Porovnání daňových systémů České a Slovenské republiky - Kraicová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalárska práca poukazuje na rozdiely v daňových sústavách Českej a Slovenskej republiky. Je zameraná na problematiku dane z príjmov fyzických osôb. Nachádza vežké odlišnosti v samotnom výpočte dane a v čiastkach znižujúcich základ dane či daň. V druhej časti práca rieši problematiku zamedzenia dvojitého zdanenia pri príjmoch plynúcich z oboch krajín. Analyzuje a vysvetžuje Smlouvu o zamezení dvojího zdanění a na príkladoch objasňuje postup riešenia rôznych situácií.

Bachelor thesis highlights the differences in the tax systems of the Czech Republic and Slovakia. It is focused on the issue of income tax of individuals. It has found large differences in the actual calculation of taxes and the amounts reducing tax base or tax. In the second part, the work deals with the avoidance of double taxation on income arising from both countries. It analyzes and explains the Convention for avoidance of double taxation and on examples of clarifying the solutions of different situations.
Comparation of Tax Systems of the Czech and Slovak Republic
Keywords: Daňový systém; daň z příjmů fyzických osob; Smlouva o zamezení dvojího zdanění mezi ČR a SR; daňový rezident ČR; daňový rezident SR; Tax system; personal income tax; Convention for avoidance of double taxation; tax resident of Czech Republic; tax resident of Slovakia